(* Title: HOL/Semiring_Normalization.thy Author: Amine Chaieb, TU Muenchen *) section \Semiring normalization\ theory Semiring_Normalization imports Numeral_Simprocs begin text \Prelude\ class comm_semiring_1_cancel_crossproduct = comm_semiring_1_cancel + assumes crossproduct_eq: "w * y + x * z = w * z + x * y \ w = x \ y = z" begin lemma crossproduct_noteq: "a \ b \ c \ d \ a * c + b * d \ a * d + b * c" by (simp add: crossproduct_eq) lemma add_scale_eq_noteq: "r \ 0 \ a = b \ c \ d \ a + r * c \ b + r * d" proof (rule notI) assume nz: "r\ 0" and cnd: "a = b \ c\d" and eq: "a + (r * c) = b + (r * d)" have "(0 * d) + (r * c) = (0 * c) + (r * d)" using add_left_imp_eq eq mult_zero_left by (simp add: cnd) then show False using crossproduct_eq [of 0 d] nz cnd by simp qed lemma add_0_iff: "b = b + a \ a = 0" using add_left_imp_eq [of b a 0] by auto end subclass (in idom) comm_semiring_1_cancel_crossproduct proof fix w x y z show "w * y + x * z = w * z + x * y \ w = x \ y = z" proof assume "w * y + x * z = w * z + x * y" then have "w * y + x * z - w * z - x * y = 0" by (simp add: algebra_simps) then have "w * (y - z) - x * (y - z) = 0" by (simp add: algebra_simps) then have "(y - z) * (w - x) = 0" by (simp add: algebra_simps) then have "y - z = 0 \ w - x = 0" by (rule divisors_zero) then show "w = x \ y = z" by auto qed (auto simp add: ac_simps) qed instance nat :: comm_semiring_1_cancel_crossproduct proof fix w x y z :: nat have aux: "\y z. y < z \ w * y + x * z = w * z + x * y \ w = x" proof - fix y z :: nat assume "y < z" then have "\k. z = y + k \ k \ 0" by (intro exI [of _ "z - y"]) auto then obtain k where "z = y + k" and "k \ 0" by blast assume "w * y + x * z = w * z + x * y" then have "(w * y + x * y) + x * k = (w * y + x * y) + w * k" by (simp add: \z = y + k\ algebra_simps) then have "x * k = w * k" by simp then show "w = x" using \k \ 0\ by simp qed show "w * y + x * z = w * z + x * y \ w = x \ y = z" by (auto simp add: neq_iff dest!: aux) qed text \Semiring normalization proper\ ML_file \Tools/semiring_normalizer.ML\ context comm_semiring_1 begin lemma semiring_normalization_rules [no_atp]: "(a * m) + (b * m) = (a + b) * m" "(a * m) + m = (a + 1) * m" "m + (a * m) = (a + 1) * m" "m + m = (1 + 1) * m" "0 + a = a" "a + 0 = a" "a * b = b * a" "(a + b) * c = (a * c) + (b * c)" "0 * a = 0" "a * 0 = 0" "1 * a = a" "a * 1 = a" "(lx * ly) * (rx * ry) = (lx * rx) * (ly * ry)" "(lx * ly) * (rx * ry) = lx * (ly * (rx * ry))" "(lx * ly) * (rx * ry) = rx * ((lx * ly) * ry)" "(lx * ly) * rx = (lx * rx) * ly" "(lx * ly) * rx = lx * (ly * rx)" "lx * (rx * ry) = (lx * rx) * ry" "lx * (rx * ry) = rx * (lx * ry)" "(a + b) + (c + d) = (a + c) + (b + d)" "(a + b) + c = a + (b + c)" "a + (c + d) = c + (a + d)" "(a + b) + c = (a + c) + b" "a + c = c + a" "a + (c + d) = (a + c) + d" "(x ^ p) * (x ^ q) = x ^ (p + q)" "x * (x ^ q) = x ^ (Suc q)" "(x ^ q) * x = x ^ (Suc q)" "x * x = x\<^sup>2" "(x * y) ^ q = (x ^ q) * (y ^ q)" "(x ^ p) ^ q = x ^ (p * q)" "x ^ 0 = 1" "x ^ 1 = x" "x * (y + z) = (x * y) + (x * z)" "x ^ (Suc q) = x * (x ^ q)" "x ^ (2*n) = (x ^ n) * (x ^ n)" by (simp_all add: algebra_simps power_add power2_eq_square power_mult_distrib power_mult del: one_add_one) local_setup \ Semiring_Normalizer.declare @{thm comm_semiring_1_axioms} {semiring = ([\<^term>\x + y\, \<^term>\x * y\, \<^term>\x ^ n\, \<^term>\0\, \<^term>\1\], @{thms semiring_normalization_rules}), ring = ([], []), field = ([], []), idom = [], ideal = []} \ end context comm_ring_1 begin lemma ring_normalization_rules [no_atp]: "- x = (- 1) * x" "x - y = x + (- y)" by simp_all local_setup \ Semiring_Normalizer.declare @{thm comm_ring_1_axioms} {semiring = ([\<^term>\x + y\, \<^term>\x * y\, \<^term>\x ^ n\, \<^term>\0\, \<^term>\1\], @{thms semiring_normalization_rules}), ring = ([\<^term>\x - y\, \<^term>\- x\], @{thms ring_normalization_rules}), field = ([], []), idom = [], ideal = []} \ end context comm_semiring_1_cancel_crossproduct begin local_setup \ Semiring_Normalizer.declare @{thm comm_semiring_1_cancel_crossproduct_axioms} {semiring = ([\<^term>\x + y\, \<^term>\x * y\, \<^term>\x ^ n\, \<^term>\0\, \<^term>\1\], @{thms semiring_normalization_rules}), ring = ([], []), field = ([], []), idom = @{thms crossproduct_noteq add_scale_eq_noteq}, ideal = []} \ end context idom begin local_setup \ Semiring_Normalizer.declare @{thm idom_axioms} {semiring = ([\<^term>\x + y\, \<^term>\x * y\, \<^term>\x ^ n\, \<^term>\0\, \<^term>\1\], @{thms semiring_normalization_rules}), ring = ([\<^term>\x - y\, \<^term>\- x\], @{thms ring_normalization_rules}), field = ([], []), idom = @{thms crossproduct_noteq add_scale_eq_noteq}, ideal = @{thms right_minus_eq add_0_iff}} \ end context field begin local_setup \ Semiring_Normalizer.declare @{thm field_axioms} {semiring = ([\<^term>\x + y\, \<^term>\x * y\, \<^term>\x ^ n\, \<^term>\0\, \<^term>\1\], @{thms semiring_normalization_rules}), ring = ([\<^term>\x - y\, \<^term>\- x\], @{thms ring_normalization_rules}), field = ([\<^term>\x / y\, \<^term>\inverse x\], @{thms divide_inverse inverse_eq_divide}), idom = @{thms crossproduct_noteq add_scale_eq_noteq}, ideal = @{thms right_minus_eq add_0_iff}} \ end code_identifier code_module Semiring_Normalization \ (SML) Arith and (OCaml) Arith and (Haskell) Arith end